Bixin Attenuates Experimental Autoimmune Encephalomyelitis by Suppressing TXNIP/NLRP3 Inflammasome Activity and Activating NRF2 Signaling - Yu, Ye; Wu, Dong-Ming; Li, Jing; Deng, Shi-Hua; Liu, Teng; Zhang, Ting; He, Miao; Zhao, Yang-Yang; Xu, Ying (Frontiers in Immunology, 2020)
Multiple sclerosis (MS), an autoimmune and degenerative disease, is characterized by demyelination and chronic neuroinflammation. Bixin is a carotenoid isolated from the seeds of Bixa orellana that exhibits various potent pharmacological activities, including antioxidant, anti-inflammatory, and anti-tumor properties. However, the effects of bixin on MS have not yet been examined. To evaluate the effects and underlying molecular mechanisms of bixin on MS, experimental autoimmune encephalomyelitis (EAE) was established in C57BL/6 mice, which were treated via intragastric administration of bixin solutions. To evaluate the molecular mechanisms of bixin, quantitative reverse-transcription PCR, western blot, immunohistochemistry, flow cytometry and enzyme-linked immunosorbent assay analyses were performed. We found that bixin significantly improved the symptoms and pathology in EAE mice, reduced the release of inflammatory cytokines TNF-α, IL-6, IL-8, IL-17 and IFN-γ, and increased the expression of the anti-inflammatory cytokine IL-10. Moreover, bixin reduced the proportion of Th1 and Th17 cells in the spleen, and suppressed microglia aggregation, and TXNIP/NLRP3 inflammasome activity by scavenging excessive reactive oxygen species (ROS) in EAE mice. Furthermore, bixin inhibited oxidative stress via activating nuclear factor erythroid 2-related factor 2 (NRF2), and its downstream genes in EAE mice, meanwhile, these effects were suppressed upon treatment with an NRF2 inhibitor, ML385. Bixin prevented neuroinflammation and demyelination in EAE mice primarily by scavenging ROS through activation of the NRF2 signaling pathway. Taken together, our results indicate that bixin is a promising therapeutic candidate for treatment of MS.